Interweaving Javanese Cultural Wisdom and Islamic Leadership Ethics: An Analysis of Arjuna in Arjunawiwaha - Fitriana, Tya Resta; Sulaksono, Djoko; Veronika, Prima; Islahuddin, Islahuddin (el Harakah: Jurnal Budaya Islam, 2025)
This study addresses the growing need to reinterpret classical Javanese figures through an Islamic ethical lens, offering a unique framework for understanding indigenous models of moral leadership. Previous studies have not yet examined how the concept of leadership in Arjuna Wiwaha can be interpreted through the framework of Islamic moral and ethical principles. Therefore, this study offers a novel perspective by integrating Javanese cultural wisdom and Islamic leadership ethics to reinterpret Arjuna’s character as a model of moral and social leadership in the Javanese-Islamic context. The aim of this paper is to examine Arjuna's leadership as depicted in the Javanese puppet story of Arjunawiwaha, focusing on the integration of Javanese social wisdom and Islamic moral leadership. In the context of Javanese-Islamic reinterpretation, Arjuna, traditionally considered a holy man in Hindu-Buddhist legends, is reimagined as a perfect pioneer. Using a cultural hermeneutic approach and comparative analysis, this investigation examines how Islamic leadership principles, including trust (Siddiq), dependability (Amanah), insight (Fathanah), and the obligation to convey the truth (Tabligh), are integrated into Arjuna's leadership narrative. The study, furthermore, highlights key Javanese social values such as humility, resilience, and wisdom, adapted from Islamic moral lessons. Through a careful examination of Arjunawiwaha, this paper illustrates a method of social adjustment and integration, which examines knowledge of how Javanese Islamic characters shape conceptualizations of governance in conventional and modern environments. The use of an interdisciplinary approach that integrates Javanese cultural wisdom and Islamic leadership ethics in analyzing the character of Arjuna in the Arjunawiwaha is a perspective still rare in leadership studies based on classical Javanese literary texts. This research thus positions the Javanese-Islamic leadership synthesis as a relevant ethical paradigm in Southeast Asia and beyond. The finding also offers a framework for culture-based leadership training integrating Javanese and Islamic values to foster ethical, culturally sensitive, and spiritually grounded leaders. Penelitian ini menanggapi meningkatnya kebutuhan untuk menafsirkan kembali tokoh-tokoh klasik Jawa melalui lensa etika Islam, dengan menawarkan kerangka unik untuk memahami model kepemimpinan moral yang bersifat lokal. Penelitian-penelitian sebelumnya belum mengkaji bagaimana konsep kepemimpinan dalam Arjuna Wiwaha dapat diinterpretasikan melalui kerangka prinsip moral dan etika Islam. Oleh karena itu, penelitian ini menawarkan perspektif baru dengan mengintegrasikan kearifan budaya Jawa dan etika kepemimpinan Islam untuk menafsirkan kembali karakter Arjuna sebagai model kepemimpinan moral dan sosial dalam konteks Jawa-Islam. Makalah ini menganalisis kepemimpinan Arjuna sebagaimana digambarkan dalam kisah pewayangan Jawa tentang Arjunawiwaha, dengan fokus pada penggabungan kearifan sosial Jawa dan moral kepemimpinan Islam. Dalam konteks penafsiran ulang Jawa-Islam, Arjuna, yang secara tradisional dianggap sebagai orang suci dalam legenda Hindu-Buddha, dibayangkan kembali sebagai seorang pelopor yang sempurna. Dengan menggunakan pendekatan hermeneutika budaya dan analisis komparatif, penyelidikan ini menyelidiki bagaimana prinsip-prinsip kepemimpinan Islam seperti kepercayaan (Siddiq), ketergantungan (Amanah), wawasan (Fathanah), dan kewajiban untuk menyampaikan kebenaran (Tabligh) dimasukkan dalam kisah kepemimpinan Arjuna. Pengkajian tersebut, lebih jauh, menyoroti nilai-nilai sosial Jawa yang utama seperti kerendahan hati, ketahanan, dan kearifan, yang diadaptasi dari pelajaran moral Islam. Melalui penelaahan Arjunawiwaha yang cermat, makalah ini menggambarkan metode penyesuaian dan integrasi sosial, yang mengkaji pengetahuan tentang bagaimana karakter Jawa-Islam membentuk konseptualisasi pemerintahan dalam lingkungan konvensional dan modern. Penggunaan pendekatan interdisipliner yang mengintegrasikan kearifan budaya Jawa dan etika kepemimpinan Islam dalam menganalisis tokoh Arjuna dalam Arjunawiwaha, sebuah perspektif yang masih jarang dalam kajian kepemimpinan berbasis teks sastra klasik Jawa. Sehingga penelitian ini bisa menempatkan sintesis kepemimpinan Jawa Islam sebagai paradigma etis yang relevan di Asia Tenggara dan sekitarnya. Temuan penelitian ini juga menawarkan kerangka pelatihan kepemimpinan berbasis budaya yang mengintegrasikan nilai-nilai Jawa dan Islam untuk membentuk pemimpin yang beretika, peka budaya, dan berlandaskan spiritual.